#TITLE_ALTERNATIVE# - MARIBUN SAMOSIR (NIM : 123 05 037); Pembimbing ; Dr. Ir. Sigit Sukmono; Sonny Winardhi, M.S, SONDANG
GETI Field located 10 km towards the west of the Prabumulih City and including one which has mature field in South Sumatra. This field has been exploited since 1938, until now still in production and the addition of some opportunities wells still developing a continued effort. Seismic characterization work of GETI Field so far not been done because the available seismic data are 2D seismic data with acquisition intervals that are very rare (more than 2 km) and the quality is also poor, while the available 3D seismic data acquisition has been doing in years 2007. Seismic reservoir characterization is a process to describe reservoir as qualitatively/quantitatively using seismic data. There are a lot of seismic methods to do this job, but at this writing only one method will be described that is simultaneous inversion. The word simultaneous means that the extraction of acoustic parameters (Vp, Vs and density) is done simultaneously, as opposed to the method of EI, EEI and Intercept - Gradient where acoustic parameters extraction is done separately/individually. The basic principle method of simultaneous inversion is the relationship between Vp and the density as seen in the Gardner’s equation and the relationship between Vp and Vs as shown in Castagna’s equation. In April 2010 has made a full sonic waveform logging known as dipole shear wave imaging in the new well (SMS-90). This loging is the first logging in the GETI Field which produces information log Vp and log Vs. The result of both logging information is then carried out a crossplot between the parameters of the log and see that the parameter Vp /Vs ratio’s can separate the sandstone and shale lithology. Based on the information of these wells and then attempted to localize the spread of these sandstones.